Periphery of education and the sociometabolism of capital in Angola: The failure of the political emancipation of the working class from 1975 to the present - Mateus , José Dias (Seven Editora, 2023)
This article is a space in which the issues related to Education in the Angolan capitalist periphery are debated, as an ideological instrument by which the sociometabolism of capital becomes real, always with the imperatives of making the political emancipation of the working class fail, knowing that dialectically, the worker is not only a reason for exploitation of the capitalist class,   It's also his biggest problem.  DOI:https://doi.org/10.56238/ptoketheeducati-035